PENERAPAN AUGMENTED REALITY (AR) UNTUK PEMETAAN GEDUNG KAMPUS UNIDAYAN MENGGUNAKAN ANDROID - LM. Fajar Israwan; Muhammad Mukmin; Siti Khadijah J (JURNAL INFORMATIKA, 2022)
Dayanu Ikhsanuddin University or better known as Unidayan is the first private university on Buton Island, located in Baubau City. The Unidayan campus consists of faculties located in different buildings. It takes time for different building layouts to determine the location of the faculty or study program as well as the intended lecture hall, therefore an application is needed that can make it easier for students to find out the location of the rooms in the faculty building. This study aims to design an application for the recognition of the Unidayan campus building using Android-based AR technology. The research resulted in an android application with Augmented Reality technology as an introduction media for Unidayan campus buildings with QR Code objects to display building plans.